Hydrated clay for catalyst removal in copper mediated atom transfer radical polymerization(a) - Munirasu, Selvaraj; Deshpande, Ashwini; Baskaran, Durairaj (Macromolecular Rapid Communications, 2008)
A simple method has been described to remove catalyst from the copper mediated atom transfer radical polymerization (ATRP) of benzyl methacrylate and methyl methacrylate in anisole at 25 degrees C using hydrated natural clay (sodium montmorillonite, Na-clay). The method consists of (1) addition of hydrated clay (CU(I/)clay approximate to 5 wt.-%) either during or after the polymerization, (2) oxidation of catalyst complex by exposing the terminated reaction mixture in air, and (3) filtration to obtain catalyst free polymer solution. A strong coordination of CuBr-ligand complex onto hydrated clay (10 wt.-%
Keywords: Atom transfer radical polymerization (ATRP); Catalysts; clay; selectivity; synthesis